2007
DOI: 10.1194/jlr.m700039-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte differentiation-related protein is induced by LRP1-mediated aggregated LDL internalization in human vascular smooth muscle cells and macrophages

Abstract: Aggregated LDL (agLDL) is internalized by LDL receptor-related protein (LRP1) in vascular smooth muscle cells (VSMCs) and human monocyte-derived macrophages (HMDMs). AgLDL is, therefore, a potent inducer of massive intracellular cholesteryl ester accumulation in lipid droplets. The adipocyte differentiation-related protein (ADRP) has been found on the surface of lipid droplets. The objectives of this work were to analyze whether agLDL uptake modulates ADRP expression levels and whether the effect of agLDL inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 37 publications
5
38
0
Order By: Relevance
“…Lipids from CFP-Plin2 overexpressing and control cell homogenates including CE, DG, TG, Chol, and total phospholipids were extracted and analyzed as described in MATERIALS AND METHODS. Consistent with other work that shows increased expression of Plin2 promotes cellular lipid accumulation (29,48,50,51), levels of TG and CE, interior core neutral lipids, were increased 1.9-and 1.7-fold, respectively in CFP-Plin2-expressing cells (Fig. 6A, P Ͻ 0.02), In addition, levels of total phospholipids, found in the surface layer of lipid droplets, were each increased 1.5-fold in CFP-Plin2-expressing cells (Fig.…”
Section: Specificity Of Cfp-plin2 Targeted Interactions Determined Bysupporting
confidence: 92%
“…Lipids from CFP-Plin2 overexpressing and control cell homogenates including CE, DG, TG, Chol, and total phospholipids were extracted and analyzed as described in MATERIALS AND METHODS. Consistent with other work that shows increased expression of Plin2 promotes cellular lipid accumulation (29,48,50,51), levels of TG and CE, interior core neutral lipids, were increased 1.9-and 1.7-fold, respectively in CFP-Plin2-expressing cells (Fig. 6A, P Ͻ 0.02), In addition, levels of total phospholipids, found in the surface layer of lipid droplets, were each increased 1.5-fold in CFP-Plin2-expressing cells (Fig.…”
Section: Specificity Of Cfp-plin2 Targeted Interactions Determined Bysupporting
confidence: 92%
“…This, in turn, induces LRP1 overexpression (34,42,43) and thus a positive feedback loop that efficiently transforms hVSMCs into foam cells (29,30). These foam cells synthesize and release increased amounts of tissue factor, a key element in the prothrombotic transformation of the vascular wall and thus in the progression of atherosclerosis to thrombosis (44).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal half of LRP1 domain CR9 Is Crucial for AgLDL-induced SREBP-2 Down-regulation and LRP1 Overexpression in hVSMCs-Previous studies from our group have demonstrated that AgLDL positively modulates LRP1 gene expression and protein levels (34,42,43), generating a positive feedback loop that efficiently transforms hVSMCs into foam cells (30). Down-regulation of sterol regulatory element-binding protein 2 (SREBP-2) plays a crucial role in the positive modulation of LRP1 by AgLDL (34,42,43).…”
Section: ) Is Crucial For Agldl Binding and Internalization In Hvsmcs-mentioning
confidence: 97%
See 1 more Smart Citation
“…38,39 Lipid droplets, in addition to accumulated glycogen granules, account for the histologic clearness of the cells. Moreover, papillary carcinomas are associated with abundant lipid-laden macrophages.…”
Section: Discussionmentioning
confidence: 99%